Predictors of attitude towards seeking counseling help among Indian University students: a case study at Jawaharlal Nehru University (JNU),New Delhi,India - Ssekamanya, Siraje Abdallah; Arshad, Munira (2010)
The purpose of the study was to find how age, gender, previous counselling experience, level of education and relationship status are related to attitudes toward seeking professional psychological help. Two hundred Jawaharlal Nehru University Students responded to the Attitude Toward Seeking Professional Psychological Help Scale (ATSPPHS) uestionnaire. The ATSPPHS consists of four subscales: Need (recognition of need), StigmaTolerance (the degree of tolerance against stigma associated with help-seeking action), Openness (interpersonal openness), and Confidence (confidence in mental health professionals). It was hypothesised that Indian university students would have negative attitude towards seeking counselling help. It was further hypothesised that gender, level of education, age, previous counselling experience and relationship status would have significant impact on the attitude towards seeking counselling help as measured by ATSPPHS. The study found that gender and level of education were the major predictors of attitude towards counselling. In particular, female Indian University students and postgraduate students had positive attitude towards seeking counselling. Overall , the study found that Indian university students had a positive attitude towards seeking counselling help. Interestingly, Indian university students were found to have scored high for Need, Openness and Confidence subscales of the ATSPPHS. However, Indian university students had low scores on the Stigma Tolerance subscale, indicating that a barrier still exists. Nevertheless, a unique finding related to this study was that students who have not received previous counselling help reported a significant positive attitude towards seeking counselling help in the future compared to those who have had received counselling help previously. The present finding could be due to the present state of counselling services in India with unprofessional or para-counsellor who may not be expert in handling the issues, hence clients may not have benefitted from the sessions or had an unpleasant experience. This finding was contradictory with the past research. Nevertheless, the findings can also be concluded into that the Indian population is ready to overcome the stigma barrier to seek counselling help when the need arises given that counsellors need to be professional and skilful.